2008
DOI: 10.1364/ol.33.000393
|View full text |Cite
|
Sign up to set email alerts
|

Data encoding on terahertz signals for communication and sensing

Abstract: We demonstrate and analyze data modulation of terahertz (THz) signals in the 1 Mbit/s range. THz pulse trains are phase and amplitude encoded with pseudorandom binary data, transmitted over a short distance, and detected. Different modulation formats are generated. Bit error measurements characterize the communication channel. We estimate from experimental results the maximum data rates for an optimized system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Due to the high resistivity and extremely short carrier trapping time (~200 fs) of LTGGaAs, carrier drift time, dark current and depletion layer thickness are of considerably less importance for the construction of high-power, highspeed LTG-GaAs-based photodiodes. LTG-GaAs-based metal-semiconductor-metal photodiodes [62][63][64], photoconductive dipole antennas (PDAs) [8,65,66], and p-i-n photodiodes [59,67] with extremely high saturation peak output power and wide O-E bandwidth have been demonstrated. High-power LTG-GaAs-based photodiodes have been used with planar-circuit broadside antennas, including planar dipole, slot and spiral antennas [68].…”
Section: Millimeter-wave Photonic Transmittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high resistivity and extremely short carrier trapping time (~200 fs) of LTGGaAs, carrier drift time, dark current and depletion layer thickness are of considerably less importance for the construction of high-power, highspeed LTG-GaAs-based photodiodes. LTG-GaAs-based metal-semiconductor-metal photodiodes [62][63][64], photoconductive dipole antennas (PDAs) [8,65,66], and p-i-n photodiodes [59,67] with extremely high saturation peak output power and wide O-E bandwidth have been demonstrated. High-power LTG-GaAs-based photodiodes have been used with planar-circuit broadside antennas, including planar dipole, slot and spiral antennas [68].…”
Section: Millimeter-wave Photonic Transmittersmentioning
confidence: 99%
“…As can be seen from the figure, the slot antenna provides much higher output power in the 1-2 THz frequency regime compared with the spiral antenna due to the characteristic resonance of the slot antenna [68]. These LTG-GaAs-based PDAs have been successfully used for wireless linking at center frequencies of around 0.3 THz [65,66]. However, the data rate so far achieved is low (~1 Mbit s -1 ) [65] and limited by the repetition rate of the Ti:sapphire laser (~80 MHz).…”
Section: Millimeter-wave Photonic Transmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, there has been a tremendous growth in THz technology. Many potential applications, including medical diagnostics [2,3], spectroscopy of biomolecules [4], security [5][6][7], and communications [8,9], have been explored. A number of significant studies have motivated the need for THz spectroscopy of liquids, including characterizing hydration state in solution [10], investigation of inflammable liquids [11], solvent diffusion in polymers [12], solvation dynamics of liquid mixtures [13,14], spectroscopy of liquid using evanescent field of a silicon waveguide [15], characterization of aqueous alcohol solutions in bottles [16], microfluidic devices for THz spectroscopy of biomolecules [17], and spectroscopy of liquids using double-modulated differential time-domain spectroscopy [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key components is the modulator. Liu et al and Möller et al have demonstrated direct modulation of terahertz sources by applying a modulation signal onto the photoconductive antennas in a terahertz time domain spectroscopy system [2,3]. A modulation rate of 1 Mbit/s and bandwidth of 23 kHz was achieved.…”
mentioning
confidence: 99%